Mejoramiento del desarrollo urbano con proyectos habitacionales tipo VIS en Neiva, Huila (2021)
The objective of this degree project is to develop an architectural urban design in the southwest of the city of Neiva, with the aim of reducing the housing deficit in the city and improving the quality of life through the approach of public space, connections with existing complementary facilities in the sector, green areas and road networks, since in Huila there are municipalities with a high rate of housing deficit. Therefore, this research has a mixed approach, where information was collected quantitatively and qualitatively, through interviews, study of data from different authors and figures from official sources, also, the urban area of Neiva is analyzed, some areas of influence and references at national and Latin American level, in order to filter the main tools and strategies implemented.